Corrossion behavioir of zinc plated 1018 steel in tomato fluid (2010)
"This research work investigated the corrosion resistance of zinc plated 1018 steel in tomato fluid. It simulated the effect of continuous use of the material in a tomato environment where corrosion products are left in place. 1018 steel samples were zinc electroplated at voltages between 0.5V to 0.9V for 5 to 20minutes.The plated samples were then subjected to tomato fluid environment for 30 days. The electrode potentials mV (SCE) were measured every day. Weight loss was determined at intervals of 5 days for the duration of the exposure period.The result showed corrosion attack on the zinc- plated steel, the severity increasing with the increasing weight of zinc coating on substrate. The result showed that thinly plated 1018 steel generally did not have any advantage over unplated steel and were quickly stripped of their zinc plating with resultant corrosion of the underlying steel substrate. Heavily zinc-plating steel was observed to offer some form of protection for the plated steel.The pH of the tomato solution which initially was acidic was observed to progress to neutrality after 5 days and then became slightly alkaline at the end of the thirty days test (because of corrosion product contamination of the tomato) contributing to the reduced corrosion rates in the plated samples after 10 day. Zinc coating of 1018 steel was found to be unsuitable for the fabrication of tomato processing machinery in this environment.